Monthly Variation in Mycosporine-like Amino Acids from Red Alga Dulse (Devaleraea inkyuleei, Formerly Palmaria palmata in Japan) - Ryuya Yamamoto; Martin Alain Mune Mune; Yoshikatsu Miyabe; Hideki Kishimura; Yuya Kumagai (Phycology, 2023)
Mycosporine-like amino acids (MAAs) are natural ultraviolet-absorbing compounds found in microalgae and macroalgae. MAA content changes seasonally and in response to environmental factors. We previously investigated MAAs from the red alga dulse (Devaleraea inkyuleei, formerly Palmaria palmata in Japan) in Usujiri, Hokkaido, Japan, from 2019 to 2020. At that time, some factors affecting MAA content were still unclear. In this study, we investigated MAA variation during the period from January to June 2021, and evaluated new methods of MAA extraction from dulse. We recorded a maximum MAA extraction yield (7.03 µmol/g dry weight) on 25 March 2021. Over the course of our three years of investigations from 2019 to 2021, we found that dulse was most suitable for MAA preparation from the middle of February to late April. In the later work reported in this paper, we improved our extraction method by using a lower-risk organic solvent (ethanol) rather than methanol. In addition, we evaluated MAA extraction using different levels of ethanol concentration (25, 50, and 99%) and different extraction times (2, 6, and 24 h). We found that extraction with 25% ethanol for 24 h increased MAA content by a factor of 3.2, compared with our previous extraction method. In summary, we determined the most suitable sampling period for Usujiri dulse, to extract the highest content of MAAs. We also improved the effectiveness of the extraction process.